Conductive liquid metal elastomer thin films with multifunctional electro-mechanical properties. Issue 4 (12th November 2020) - Tahidul Haque, A B M; Tutika, Ravi; Gao, Meng; Martinez, Angel; Mills, Julie; Arul Clement, J; Gao, Junfeng; Tabrizi, Mohsen; Ravi Shankar, M; Pei, Qibing; Bartlett, Michael D
Abstract: Wearable electronics, conformable sensors, and soft/micro-robotics require conductive yet stretchable thin films. However, traditional free standing metallic thin films are often brittle, inextensible, and must be processed in strict environments. This limits implementation into soft technologies where high electrical conductivity must be achieved while maintaining high compliance and conformability. Here we show a liquid metal elastomeric thin film (LET) composite with elastomer-like compliance (modulus < 500 kPa) and stretchability (>700%) with metallic conductivity (sheet resistance < 0.1 Ω/□). These 30–70 µ m thin films are highly conformable, free standing, and display a unique Janus microstructure, where a fully conductive activated side is accompanied with an opposite insulated face. LETs display exceptional electro-mechanical characteristics, with a highly linear strain-resistance relationship beyond 700% deformation while maintaining a low resistance. We demonstrate the multifunctionality of LETs for soft technologies by leveraging the unique combination of high compliance and electrical conductivity with transfer capabilities for strain sensing on soft materials, as compliant electrodes in a dielectric elastomeric actuator, and as resistive heaters for a liquid crystal elastomer.